2017
DOI: 10.1038/s41598-017-09310-1
|View full text |Cite
|
Sign up to set email alerts
|

Ocular fundus pulsations within the posterior rat eye: Chorioscleral motion and response to elevated intraocular pressure

Abstract: A multi-functional optical coherence tomography (OCT) approach is presented to determine ocular fundus pulsations as an axial displacement between the retina and the chorioscleral complex in the albino rat eye. By combining optical coherence elastography and OCT angiography (OCTA), we measure subtle deformations in the nanometer range within the eye and simultaneously map retinal and choroidal perfusion. The conventional OCT reflectivity contrast serves as a backbone to segment the retina and to define several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…[36][37][38] Our group adapted PS-OCT for preclinical imaging of the rodent eye 39,40 and recently extended the method to a multifunctional OCT retinal imaging approach. 41,42 In our past study of the VLDLR knockout mouse model, we introduced a multifunctional OCT approach enabling a description of longterm retinal changes occurring between 1 and 11 months of age. 41 One limitation of that study was the rather late baseline measurement only after neovascularizations, which in the mutant mice usually form between postnatal day (P)14 and P21 12 and had already been well developed.…”
Section: Conclusion Longitudinal Multifunctional Oct Imaging Of Inmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] Our group adapted PS-OCT for preclinical imaging of the rodent eye 39,40 and recently extended the method to a multifunctional OCT retinal imaging approach. 41,42 In our past study of the VLDLR knockout mouse model, we introduced a multifunctional OCT approach enabling a description of longterm retinal changes occurring between 1 and 11 months of age. 41 One limitation of that study was the rather late baseline measurement only after neovascularizations, which in the mutant mice usually form between postnatal day (P)14 and P21 12 and had already been well developed.…”
Section: Conclusion Longitudinal Multifunctional Oct Imaging Of Inmentioning
confidence: 99%
“…In this work we utilized a multifunctional OCT imaging system that was described in detail by Fialová et al 43 and has been recently used to image mouse 41 and rat models 42,44 of ophthalmic diseases. In short, the system is based on a SD, PS-OCT unit enabling high-speed retinal imaging at 83-kHz Ascan rate with an axial resolution of 3.8 lm in retinal tissue.…”
Section: Multifunctional Optical Coherence Tomographymentioning
confidence: 99%
“…Zhi et al 20 reported that choroidal and optic nerve head perfusions measured using OCT microangiography were more resistant to IOP elevation than retinal perfusion. Augustin et al 25 used OCT to measure vessel pulsatility as an index of blood flow (or flux) and studied the effect of IOP elevation on the superficial retinal plexus and the deeper retinal capillary plexus at the rat optic nerve head. They showed that significant attenuation of flux occurred at a high IOP of 95 mm Hg for the deeper capillary plexus compared with 85 mm Hg for the superficial vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kornfield and Newman 24 showed that flickering light stimulation in rat retina evoked greater vasodilation in the intermediate capillary layer compared with superficial and deep capillary layers. Data reported by Augustin et al 25 suggest that at high IOP, above 65 mm Hg, deeper retinal vessels in the rat retina were more attenuated than the superficial vessels. Therefore, it remains unclear whether differences exist between the way the various vascular layers autoregulate against IOP elevation.…”
mentioning
confidence: 82%
“…Although many of the OP measurement techniques require contact with the ocular surface, others enable noncontact, in vivo OP measurement. In particular, laser and low-coherence interferometry20,24,30,31 and Fourier-domain optical coherence tomography (OCT)23,32 were proposed to register OP. The latter has been used for noninvasive and simultaneous measurement of the movements of cornea and retina.…”
Section: Introductionmentioning
confidence: 99%